Development and validation of a tool to assess knowledge, attitudes, and practices toward diet sustainability - Hilary, Serene; Safi, Samir; Sabir, Rubina; Numan, Asma Bahaaldeen; Zidan, Souzan; Platat, Carine (Frontiers in Sustainable Food Systems, 2024)
This study aimed to develop and validate an instrument, the Sustainable Diets Questionnaire (SDQ), to assess the knowledge, attitude, and practice of sustainable diets in adult populations. A panel of four nutritionists identified 63 items through a literature review and refined them to a 54-item model for validation across four domains: Knowledge domain (K, eight items), Attitude domain (A, 18 items), Practice domain (P, 16 items) and Consumption Habits domain (D, 12 items). The validation process consisted of a pilot with 86 individuals (Phase 1) and a larger study with 389 participants (Phase 2). Confirmatory Factor Analysis (CFA) was conducted in both phases to verify model fit. In Phase 1, the initial four-factor model did not converge, indicating a need for item modification and a revised three-factor model (K domain, eight items; A domain, 18 items; new P domain, 28 items). In Phase 2, the new model showed improvement in fit indices with a Scaled Chi-Square of 2.415, Comparative Fit Index (CFI) of 0.863, Goodness of Fit Index (GFI) of 0.747, Tucker-Lewis Index (TLI) of 0.851 and the Root Mean Square Error (RMSE) was 0.066, although some indices fell below the 0.9 threshold. The Cronbach’s α for the Knowledge, Attitude, and Practice domains were 0.9, 0.96, and 0.897, respectively, with an overall α of 0.959. There was no significant difference between the first and second attempts of the SDQ model, indicating good test–retest reliability. There was also a significant positive correlation between the response scores of K, A, and P domains (K vs. A, r = 0.575, p < 0.001; K vs. P, r = 0.496, p ≤ 0.001 and A vs. P, r = 0.665, p ≤ 0.001). The study concludes that the three-factor model of SDQ is a valid and reliable tool for understanding the knowledge, attitudes, and practices of sustainable diets among adults.